Aspects of Pelvic Floor Protection in Spontaneous Delivery – a Review - Hübner, Markus; Rothe, Christiane; Plappert, Claudia; Baeßler, Kaven (Geburtshilfe und Frauenheilkunde, 2022)
The necessity of increasingly addressing aspects of pelvic floor protection, i.e., prevention of the most frequent female pelvic floor disorders, such as urinary incontinence, faecal incontinence and pelvic organ prolapse, is the result of the steadily improving understanding of the association of pregnancy and delivery with the prevalence of these disorders. About a quarter of all women experience one or more such symptoms during their life. Apart from age and weight, pregnancies and births play an important part. While initial discussion of pelvic floor protection often focused very rapidly on the mode of delivery and elective caesarean section as a possible protective intervention, it has become apparent in the last few decades how varied and wide-ranging the options are that can be used to protect against pelvic floor disorders. The mode of delivery as such is “only” one element among numerous other considerations and has diminished markedly in importance. Interprofessionality and interdisciplinarity undoubtedly represent an important development as resulting recommendations must always be incorporated in an overall context that considers mother and child at the same time. Considering the pelvic floor only certainly does not make sense. This review article will analyze in greater detail important pre-, intra- and postpartum aspects that in their entirety can provide insight into the various aspects of pelvic floor protection. The authors regard the following article as an additional basis for discussion on achieving a sustained reduction in the incidence and prevalence of female pelvic floor disorders.
Keywords: vaginal delivery; pelvic floor protection; pelvic floor rehabilitation; urinary incontinence; pelvic organ prolapse; faecal incontinence; pregnancy